Delivering, funding, and rating safe staffing levels and skills mix in aged care. (July 2021) - Peters, Micah D.J.; Marnie, Casey; Butler, Annie
Abstract: Background: Staffing levels and skill mix are critical issues within residential aged care. The positive impact of a sufficient number and skills mix of staff is upheld by abundant evidence within and beyond the sector. While being able to determine suitable staffing levels and skills mix to provide care to nursing home residents is vital, having an appropriate approach to funding the delivery of care is also critical. Beyond determining staffing levels and skills mix and funding care delivery, transparently rating the adequacy of staffing is also important to enable informed decision-making amongst consumers, policy makers, staff, and other stakeholders. There are existing tools for determining nursing home staffing levels and skills mix, funding care, and rating and reporting staffing, however there appears to be ongoing confusion regarding how these different tools might work together to achieve different things in order to ensure safe, quality care. Objectives: In order to explain the importance of ensuring at least a minimum number (staffing level) of the right kind of staff (skills mix) to provide care to nursing home residents, in this paper we briefly explain key differences and interrelationships between three tools; one for determining staffing and skills mix, one for determining funding, and one for rating and reporting the level of staffing within a facility as a measure of quality. Results: Our explanation of the three existing tools has resulted in the development of a conceptual model for how minimum staffing levels and skills mix supports the delivery of safe, quality care and how this can be understood in relation to determining, funding, and rating staffing levels and skills mix. Conclusions: Our conceptual model of how determining, funding, and rating staffing levels and skills mix relate to one another and fulfil different but related purposes can be used to demonstrate how minimum staffing levels and skills mix can be understood as foundational to ensuring respectful, safe, quality care.